Development of foil fencing with particular emphasis on judging methods - Witkowski, Andrzej; Muszkieta, Radosław; Jarosławski, Leszek (Journal of Education, Health and Sport, 2025)
The article provides a concise overview of the history of combat using bladed weapons, as well as the origins of sporting activities, which were already observed in ancient Egypt, predating the ancient Greek games by more than 400 years. It describes the development of the art of fencing from knightly tournaments to modern competitive fencing, highlighting important events that influenced the development of fencing: - the introduction of the foil as a new type of weapon, - the introduction of the fencing mask, - the introduction of electrical equipment to assist the referee. The role of the referee in modern sport fencing is characterised and the methods of refereeing in foil fencing are described in detail: from the period of using the so-called ordinary foil (with five referees) to modern times, i.e. the use of electrical apparatus, video verification and the replacement of verbal analysis of fencing actions with appropriate hand gestures. Finally, fencing is briefly characterised as a sport in which the physical, intellectual and mental qualities of the competitors play an important role, and fencing is described as a kind of intellectual game played between two competitors-opponents, in which intelligence and creative thinking are of great importance.